2019
DOI: 10.1002/adfm.201970239
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Luminescence: Circularly Polarized Luminescence Induced by Chiral Super Nanospaces (Adv. Funct. Mater. 35/2019)

Abstract: In article number 1903246, Fumito Araoka, Suk‐Won Choi, and co‐workers demonstrate circularly polarized luminescence (CPL) from a nanosegregated mesophase consisting only of achiral molecules. CPL is induced through self‐assembled chiral aggregates (in the chiral super nanospace) formed only by achiral molecules. The results introduce the possibility of developing a novel technique for constructing practical CPL active materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…As such, ongoing studies include adoption of deep learning techniques in the hierarchical verification method to reduce the angle dependency. 41 Foregoing efforts include increasing the encoding capacity of the PUFs by modifying the HNF surface with guest materials such as nanoparticles 9,42 and fluorophores 43 to tune the chiroptical properties. We highlight that our method of utilizing randomness found in nature can be critical for designing next-generation security technologies to combat evolving adversaries.…”
Section: Discussionmentioning
confidence: 99%
“…As such, ongoing studies include adoption of deep learning techniques in the hierarchical verification method to reduce the angle dependency. 41 Foregoing efforts include increasing the encoding capacity of the PUFs by modifying the HNF surface with guest materials such as nanoparticles 9,42 and fluorophores 43 to tune the chiroptical properties. We highlight that our method of utilizing randomness found in nature can be critical for designing next-generation security technologies to combat evolving adversaries.…”
Section: Discussionmentioning
confidence: 99%
“…Chiral structures obtained by surface modification of inorganic nanomaterials using chiral ligands or by self‐assembly of inorganic nanomaterials with chiral templates can interact strongly with photons and cause changes in polarization states to produce CPL [34,37,39,70–74] …”
Section: Mechanistic Investigation Of the Cpl Activity From Ccdsmentioning
confidence: 99%
“…In recent years, more attention has been paid to CCDs with respect to their chiral origin, potential applications and optical phenomena [30] . The potential applications are currently mainly in the biological field, and the optical phenomena have been well‐developed in recent years for two‐photon absorption [30–33] and CPL [34,37] . The photoluminescence (PL) mechanism of CDs is still unclear due to the complexity of their core‐shell structure and the diversity of surface functional groups [35] .…”
Section: Introductionmentioning
confidence: 99%
“…B.-C. Kim et al demonstrated CPL activity in a liquid crystalline mesophase obtained from the assembly of achiral molecules. 141 The authors employed a 1 : 1 mixture of a rod-shaped molecule (blended with a small amount of pyrromethene dye) and a bent-core host system. In the mixed state, dye molecules follow a mesogen ordering pattern.…”
Section: Supramolecular Self-/co-assembly and Cplmentioning
confidence: 99%